Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Given the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] below, find [tex]\( g(f(0)) \)[/tex].

[tex]\( f(x) = 4x + 1 \)[/tex]

[tex]\( g(x) = 5x - 3 \)[/tex]


Sagot :

To find [tex]\( g(f(0)) \)[/tex] given the functions [tex]\( f(x) = 4x + 1 \)[/tex] and [tex]\( g(x) = 5x - 3 \)[/tex], we need to follow these steps:

1. Evaluate [tex]\( f(0) \)[/tex]:
[tex]\[ f(x) = 4x + 1 \][/tex]
Substitute [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = 4(0) + 1 = 1 \][/tex]

2. Use the result of [tex]\( f(0) \)[/tex] to find [tex]\( g(f(0)) \)[/tex]:
We have found that [tex]\( f(0) = 1 \)[/tex].

3. Evaluate [tex]\( g(1) \)[/tex]:
[tex]\[ g(x) = 5x - 3 \][/tex]
Substitute [tex]\( x = 1 \)[/tex]:
[tex]\[ g(1) = 5(1) - 3 = 5 - 3 = 2 \][/tex]

Therefore, [tex]\( g(f(0)) = g(1) = 2 \)[/tex].

Summarizing the results:
- [tex]\( f(0) = 1 \)[/tex]
- [tex]\( g(f(0)) = 2 \)[/tex]

So, [tex]\( g(f(0)) = 2 \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.